EDUCATIONAL VALUES FROM CONCEPTUAL METAPHORS OF BATAK TOBA LANGUAGE PROVERBS: A COGNITIVE SEMANTIC APPROACH - Sirait, Asnita (English Education Department of STKIP Pasundan, 2023)
Proverbs contain messages, advice, criticism, punishment, and allusions. However, understanding proverbs need more effort due to the metaphorical expressions used in chaining the words. Therefore, the objectives of this study are toto investigate what values are contained in the Batak Toba language which can then be applied in the world of education and to draw a conceptual metaphor of how the Toba Batak culture is shown in a conceptual metaphor. Conceptual metaphors are studied from cognitive semantics, which also studies how to know the human mind through a mapping. This study is a qualitative descriptive study using the theory of conceptual metaphor from Lakoff and Turner (1989) and Lakoff and Johnson (1999) who developed the Conceptual Metaphor Theory, or CTM, which has been followed and subsequently improved over the years by various scholars. The study found that in BTL. Interpreting the intention and meaning in the proverbs metaphorical expression can be done through a semantic cognitive approach by mapping the source domain to target domain (A → B) concept. The conceptual metaphor found in the proverbs are humbleness is hand down, giving is hand hiding, an empty hand is someone’s inability, Shoulder is a hard surface for containment, eyes are teachers, hair is the size of problem, careful thought is wetted lips, and empty stomach is a danger. The study also found educational values from the proverb applied in educational institution.